Reaching women with obesity to support weight loss before pregnancy: feasibility and qualitative assessment - Denise Simon; Anjali J. Kaimal; Emily Oken; Marie-France Hivert (SAGE Publishing, 2020)
Background: We sought to assess attitudes toward weight and barriers to recruitment of women with obesity for a potential preconception weight-loss/lifestyle modification intervention. Methods: We performed a qualitative study involving women of reproductive age (18-45) with obesity (body mass index ⩾30 kg/m 2 ) who were considering a pregnancy in the next 2 years. We evaluated four methods of recruitment. We used previously validated survey questions to evaluate risk perceptions. In a subset, we used semistructured interviews for topics that required more in-depth information: domains included attitudes toward weight-related issues, intentions, and barriers to engagement in a structured weight-loss program. We performed qualitative analyses of interview transcripts using immersion crystallization. Results: We recruited the majority (80/82, 98%) of women using e-recruitment strategies. Eighty-one women filled out the survey and 39 completed an interview. Three-quarters of the women surveyed (60 of 81) reported attempts to lose weight in the past year and 77% (68/81) of survey respondents cited jobs and work schedules as a barrier to adopting healthy habits. More than 87% (34 of 39) of women interviewed reported willingness to participate in a structured weight-loss program prior to getting pregnant. Of these, 74% (25 of 34) stated they would consider delaying their attempts at a future pregnancy in order to participate in such a program. Conclusions: E-recruitment is a promising strategy for recruitment for preconception weight-loss and lifestyle modification program. Most women state a willingness to delay pregnancy attempts to participate in a weight-loss program.